Inhibition of Mild Steel Corrosion in Phosphoric Acid using Allyl Methyl Sulfide - Balanaga Karthik, B. (Asian Journal of Chemistry, 2011)
The effect of allyl methyl sulfide on the corrosion of mild steel in a solution of phosphoric acid has been investigated by weight loss method in relation to the concentration of the inhibitor and acid as well as the temperature. At room temperature, the efficiency of the inhibition increases with concentration of allyl methyl sulfide increases for mild steel. Corrosion rate is maximum for uninhibited solution as compared to the inhibited solution at all temperature. Corrosion rate is increases with increase of temperature. For 1 × 10-2 M of allyl methyl sulfide concentration, the percentage efficiency decreases with the temperature increases because of decreasing adsorption with increase in temperature. Low heat of adsorption indicates the adsorption is only physical in nature. By increasing the temperature, the free energy change values decreases. This shows that increase in temperature favours the corrosion process. As the concentration of the inhibitor decreases the free energy change increases. This shows that with decrease in concentration of allyl methyl sulfide the corrosion process becomes more and easier.